The parasitoid communities associated with Ceutorhynchus species (Coleoptera: Curculionidae) in Ontario and Québec, Canada*. Issue 2 (13th February 2014) - Mason, P.G.; Miall, J.H.; Bouchard, P.; Brauner, A.; Gillespie, D.R.; Gibson, G.A.P.
Abstract Surveys were conducted in Ontario and Québec, Canada to determine the parasitoid communities associated with Ceutorhynchus Germar (Coleoptera: Curculionidae) weevil species that are potential nontarget hosts of candidate biological control agents of the cabbage seedpod weevil, Ceutorhynchus obstrictus (Marsham). New host plant associations are documented for Ceutorhynchus americanus Buchanan, Ceutorhynchus neglectus Blatchley, and Ceutorhynchus omissus Fall. More than 18 species of Chalcidoidea (Hymenoptera) were associated with six Ceutorhynchus species reared from siliques and stems of Brassicaceae plants. Silique-feeding Ceutorhynchus species supported a more diverse parasitoid community than stem-feeding or root crown-feeding species. The major components of the parasitoid assemblage of the native C. neglectus included Mesopolobus gemellus Baur and Muller, Mesopolobus moryoides Gibson, Trichomalus lucidus (Walker) (Hymenoptera: Pteromalidae) and a cryptic species complex previously reported as Necremnus tidius (Walker) (Hymenoptera: Eulophidae). These species, plus Trimeromicrus maculatus Gahan (Hymenoptera: Pteromalidae) were the main parasitoids attacking the native C. omissus. The major parasitoids associated with the accidently introduced Ceutorhynchus erysimi (Fabricius) and Ceutorhynchus typhae (Herbst) included T. maculatus, the N. tidius species complex, M. gemellus, and M. moryoides. Trichomalus perfectus (Walker) (Hymenoptera: Pteromalidae), a major parasitoid of C. obstrictus in Europe, is an accidental introduction first reared in Canada from that host in 2009 and first collected from C. omissus in 2011. Mesopolobus gemellus is shown to have a broad host range. These findings highlight the need for a cautious approach before introducing new biological control agents.